A transient voltage-dependent outward current in cultured cerebellar granules. Issue 4 (August 1989) - Robello, Mauro; Carignani, Corrado; Marchetti, Carla
Abstract : Granule cells were dissociated from rat cerebella with a procedure that yields a 98% pure cell population. Potassium currents in these cells were studied using the patch-clamp technique. Depolarizing pulses of 10 mV step and 100 ms duration from a holding potential of −80 mV elicited two different potassium outward currents: a transient, low-voltage activated component and a long lasting, high-voltage activated component. At +30 mV, the total current reached an amplitude of 2 nA (mean value of 15 experiments). The reversal potential of the transient current, estimated by measuring tail currents, was −77 mV, close to that predicted by the Nernst equation. The transient current was half inactivated with a holding potential of −78 mV and completely inactivated with −50 mV or more positive holding potentials. Finally, the current decay could be fitted by the sum of two exponentials with time constants of about 20 and 250 ms.